COVID-19 Quarantine: A Key Part of Prevention in Nepal - Tamang, Pasang; Mahato, Preeti; Shahi, Prakash; Simkhada, Padam; Teijlingen, Edwin van; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2020)
As the Coronavirus (COVID-19) outbreak continues to evolve, globally, many countries have introduced preventive measures to reduce human-to-human transmission in areas where the virus that causes COVID-19 is already circulating in the population. Public health measures include quarantine, which involves the restriction of the movement of ill people from the rest of the population. With the rapid increase in the number of COVID-19 positive cases, the Government of Nepal has also introduced quarantine for the COVID-19 positive cases as well as the returning migrant workers and their accompanying family members. However, concerns over quarantine facilities in border areas of Nepal have been raised by the healthcare professionals quoting the facilities as risky. Hence, the quarantine facility needs to have minimum standards so that the infection is not spread further as well as improving the better health of those in quarantine rather than deteriorating their situation. The essentials such as adequate food, water, and hygiene provisions should be made available to the patients during the quarantine period and their health should be monitored. Other preventive measures such as social distancing and hand hygiene should be maintained within the quarantine facility.